Efeito direto e transdentinário do LED 850 nm sobre o metabolismo e capacidade de diferenciação odontoblástica de células-tronco da polpa dentária in vitro - Turrioni, Ana Paula Silveira [UNESP] (2015)
The overall aim of this study was to evaluate in vitro the effect of 850 nm LED irradiation on different metabolic processes of stem cells from human exfoliated deciduous teeth (SHEDs). For all studies, pulp cells originated from sound deciduous teeth were characterized by immunofluorescence using STRO-1, CD44, CD146, Nanog and OCT3/4 antibodies, before experimental protocols. In the first experiment, cells were seeded in 24 well-plates, submitted to ondontoblastic differentiation and irradiated with different energy doses (ED - 0, 2, 4, 8, 15 or 30 J/cm2, 40 mW/cm2) n=9. After 12 h and 72 h post irradiation, cell viability (MTT), mineralized nodule formation (MN - Alizarin Red) and number of viable cells (Trypan Blue) were evaluated. Data were submitted to Kruskal Wallis and Mann-Whitney tests (p<0.05). In the second experiment, the same protocol was performed, however, using only 2 and 4 J/cm2, considering 72 h post irradiation as period of evaluation. Alkaline phosphatase (ALP) activity, total protein (TP) production, total collagen production (Sircol Assay), as well as gene expression (qPCR) of ALP, collagen type I (Col I), dentin sialophosphoprotein (DSPP) and dentin matrix acidic phosphoprotein 1 (DMP-1) were assessed, n=8. For the third experiment, cells were seeded on the pulp surface of 0.2 mm-thick dentin discs (n=72) and submitted to the same protocol of irradiation as experiment 2, applied on the occlusal surface of the dentin discs (n=8, transdentinal action). The assays included cell viability (MTT), ALP activity, TP production, ALP, Col I, DSPP and DMP-1 gene expression and cell morphology (SEM). Again, the same statistical tests were applied to data. In the first study, when compared with the control group, cells submitted to 2 or 4 J/cm2 showed higher cell viability after 72 h and all EDs increased the number of viable cells after 12 h. For MN formation... (Complete abstract electronic access below)